On the origin of low-frequency blood pressure variability in the conscious dog. - Just, Armin; Wagner, C. D.; Ehmke, Heimo; Kirchheim, Hartmut; Persson, P. B. (The journal of physiology, 1995)
1. Baroreceptor denervation increases blood pressure variability below 0.1 Hz. This study was undertaken to determine to what extent these fluctuations originate from the central nervous system or from cardiovascular sources. 2. Blood pressure was recorded at a rate of 10 Hz for approximately 3.5 h in conscious, resting dogs. Power density spectra were calculated from all 2(17) points of each recording session and integrated between 0.0002 and 0.1 Hz. 3. Blockade of the afferent limb of the baroreceptor reflex by surgical denervation of sinoaortic and cardiopulmonary afferents (Den; n = 6) significantly increased integrated power more than sixfold compared with a control group (n = 11). 4. Impairment of the efferent limb in non-deafferented dogs by either alpha 1-adrenergic blockade with prazosin (Praz; n = 7) or ganglionic blockade with hexamethonium (Hex; n = 6) failed to raise variability. 5. Both prazosin (n = 6) and hexamethonium (n = 3) reduced the increased variability in denervated dogs. 6. In non-deafferented dogs receiving hexamethonium, elevation of mean blood pressure to the hypertensive level of the Den group, by a continuous infusion of noradrenaline (n = 4), did not change the variability. 7. It is concluded that in the absence of changes in posture, most of the increased blood pressure variability after baroreceptor denervation is derived from the central nervous system. 8. Direct comparison of power spectra of the Den (total variability) and Hex groups (variability derived from the cardiovascular system only) suggests that the central nervous system is also the prevalent source of low-frequency blood pressure variability in intact animals.
Gesehen am 25.11.2024